Penerapan Metode HOTS (Higher Order Thinking Skill) dalam Pembelajaran Bahasa Jepang di SMA - Febi Ariani Saragih (Journal of Japanese Language Education and Linguistics, 2019)
(Application of HOTS (Higher Order Thinking Skills) Method in Japanese Language Learning in Senior High School This study aims to find out how the application and inhibiting factors of the HOTS method in learning Japanese at the high school level. The scope of this research is the planning and learning process in one of the KD (Basic Competency) Japanese XI grade at SMAN 6 Malang. The process of making an evaluation, and the evaluation process itself does not belong to the scope of this study. The method used in this research was a descriptive qualitative method using Classroom Research design. Data collection techniques used non-participant observation, documentation, and interviews. The data in this study were dialogues, monologues, and activities related to the application of the HOTS method in learning Japanese. The results of this study indicated that the learning used by teachers for the application of HOTS was following the Problem Based Learning model in which there were learning processes in analyzing (C4), evaluating (C5), and creating (C6). Inhibiting factors that arose in the process of applying the HOTS method consisted of teacher doubt in planning the learning tools, differences in the understanding of each teacher in interpreting HOTS-based teaching materials, limitations of instructional media that are compatible with learning materials, inadequate school facilities, and students who tend to be passive.